Strategi Pengembangan Konten Pendidikan Islami: Memaksimalkan Potensi Era Digital - Muhammad Fajri Winanda; Farhan Nurhidayah; Pandu Fahrizal; Ahmad Rijal Hermawan; Nurjanah (PT. Pusmedia Group Indonesia, 2024)
The digital era has opened up new opportunities for the development and dissemination of Islamic content. This study aims to identify effective strategies for developing relevant and engaging Islamic content in the digital age. The research method used is library research, which involves collecting and analyzing various literature related to Islamic content development, digital technology, and digital marketing strategies. The results show that optimizing the use of social media, online video platforms, and mobile applications are key to maximizing the spread and impact of Islamic content. Furthermore, integrating Islamic values with advanced technological approaches can enhance audience engagement and broaden the scope of da'wah. This study concludes that collaboration between scholars, technology developers, and digital marketing experts is necessary to create Islamic content that is not only informative but also inspiring and easily accessible to various segments of society. These strategies are expected to support the digital transformation in spreading Islamic values and strengthen the global Muslim community. Keywords: Teaching Development; Islamic Education Content; Digital Era